The Relation of Balinese EFL Learners’ Prior Learning Experience and Present Proficiency - Pratiwi, Putu Ayu Asty Senja (Lingua Cultura, 2020)
The research tried to shed light on the relation of prior learning experience and motivation in shaping the learners’ proficiency. It investigated the importance of prior learning experience and the role of motivation in learning development. This needed to investigate further to find out how positive and negative prior learning experience with intrinsic and extrinsic motivation determined the way the students, value their phase of learning, and the relation with their present proficiency. From the empirical study of the Balinese EFL learners, there were three types of learners based on the prior learning experience and the role of intrinsic and extrinsic motivation. The first type consisted of the learners who had positive prior learning experience, had high intrinsic motivation, and gained high proficiency in their present study; the second type was those who had low intrinsic motivation but changed into high intrinsic motivation due to the extrinsic motivation; the third type was the learners who had negative prior learning experience, low intrinsic motivation, and resulted in low proficiency. In total, 15 students ranging from 19–23 years old (4 males and 11 females) voluntarily participated in the test and interview. Through the in-depth interview, it is found that the positive prior learning experience and high intrinsic motivation motivate the students and lead them to higher proficiency. However, demotivation and a low level of proficiency can occur from the negative prior learning experience and low intrinsic motivation.